Cerebrospinal fluid findings in patients with myelin oligodendrocyte glycoprotein (MOG) antibodies. Part 2: results from 108 lumbar punctures in 80 pediatric patients - Jarius, Sven; Syrbe, Steffen; Korporal-Kuhnke, Mirjam; Haas, Jürgen; Wildemann, Brigitte (Journal of neuroinflammation, 2020)
New-generation, cell-based assays have demonstrated a robust association of serum autoantibodies to full-length human myelin oligodendrocyte glycoprotein (MOG-IgG) with (mostly recurrent) optic neuritis, myelitis, and brainstem encephalitis, as well as with neuromyelitis optica (NMO)-like or acute-disseminated encephalomyelitis (ADEM)-like presentations. However, only limited data are yet available on cerebrospinal fluid (CSF) findings in MOG-IgG-associated encephalomyelitis (MOG-EM; also termed MOG antibody-associated disease, MOGAD)
Gesehen am 05.03.2021